2024
DOI: 10.1021/acs.analchem.3c03588
|View full text |Cite
|
Sign up to set email alerts
|

Single-Chain Conjugated Polymer Guests Confined inside Metal–Organic Frameworks (MOFs): Boosting the Detection and Degradation of a Sulfur Mustard Simulant

Shuya Liu,
Yongxian Guo,
Yifei Jiang
et al.

Abstract: Real-time detection and effective degradation of toxic gases have attracted considerable attention in environmental monitoring and human health. Here, we demonstrate a solventassisted dynamic assembly strategy to strongly enhance the detection and degradation performance for 2-chloroethyl ethyl sulfide (CEES, as a sulfur mustard simulant) via confinement of a conjugated polymer in metal−organic frameworks (MOFs). The conjugated polymer poly(9,9-di-n-octylfluorene-altbenzothiadiazole) (F8BT) is infiltrated into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…lanthanides and transition metals) or capturing of targeted chemicals. 45,46 Liu et al 47 demonstrated a solvent assisted dynamic assembly strategy to confine the polymer poly(9,9-di- n -octylfluorene-altbenzothiadiazole) (F8BT) in MOFs (sensor 35 ), which strongly enhanced the detection and degradation performance for CEES (Fig. 22).…”
Section: Direct Detection By Molecular Probesmentioning
confidence: 99%
“…lanthanides and transition metals) or capturing of targeted chemicals. 45,46 Liu et al 47 demonstrated a solvent assisted dynamic assembly strategy to confine the polymer poly(9,9-di- n -octylfluorene-altbenzothiadiazole) (F8BT) in MOFs (sensor 35 ), which strongly enhanced the detection and degradation performance for CEES (Fig. 22).…”
Section: Direct Detection By Molecular Probesmentioning
confidence: 99%